a) Áp dụng t/c dãy tỉ số bằng nhau, ta có:
\(\frac{x}{2}=\frac{y}{3}=\frac{y-x}{3-2}=\frac{14}{1}=14\)
=> \(\begin{cases}x=28\\y=42\end{cases}\)
b) Từ 2x = 7y => \(\frac{2x}{14}=\frac{7y}{14}\Rightarrow\frac{x}{7}=\frac{y}{2}\)
Áp dụng t/c dãy tỉ số bằng nhau, ta có:
\(\frac{x}{7}=\frac{y}{2}=\frac{x+y}{7+2}=\frac{36}{9}=4\)
=> \(\begin{cases}x=28\\y=8\end{cases}\)
c) Từ \(\frac{x}{y}=\frac{3}{7}\Rightarrow\frac{x}{7}=\frac{y}{3}\)
Áp dụng t/c dãy tỉ số bằng nhau, ta có:
\(\frac{x}{7}=\frac{y}{3}=\frac{y-x}{3-7}=\frac{20}{-4}=-5\)
=> \(\begin{cases}x=-35\\y=-15\end{cases}\)
d) Đặt \(\frac{x}{2}=\frac{y}{3}=k\Rightarrow\begin{cases}x=2k\\y=3k\end{cases}\)
Vì xy = 24 => 2k.3k = 24 => 6k2 = 24 => k2 = 4 => k = \(\pm\) 2
Với k = 2 => \(\begin{cases}x=4\\y=6\end{cases}\)
Với k = -2 => \(\begin{cases}x=-4\\y=-6\end{cases}\)
Chỉ cần áp dụng tc của dãy tỉ số bằng nhau là đc thôi mà